2016
DOI: 10.3233/cbm-160592
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation associated with CD44/CD166 immunoexpression as predictors of worse outcome in metastatic colon cancer

Abstract: An association between CD44 and CD166 expression was demonstrated in this study. Analysis of KRAS mutation combined with immunohistochemical expression of CD44 and CD166 identified subgroups of patients with colon adenocarcinoma at higher risk of lymph node involvement by the tumor and development of liver and lung metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 38 publications
1
26
2
Order By: Relevance
“…CSCs are identified by specific surface epitopes. In CRC, CD133, CD24, CD44, CD166, EpCAM, and ALDHA1 are reported as CSC markers [1518]. Cells expressing these surface epitopes have the ability to form tumors at a much diluted concentration in SCID mice that histologically resemble the primary tumor from which they were derived [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSCs are identified by specific surface epitopes. In CRC, CD133, CD24, CD44, CD166, EpCAM, and ALDHA1 are reported as CSC markers [1518]. Cells expressing these surface epitopes have the ability to form tumors at a much diluted concentration in SCID mice that histologically resemble the primary tumor from which they were derived [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several stages of carcinogenesis in colon cancer comprise subpopulations of CSCs, which are responsible for tumor cell transformation, growth, and proliferation. Recently, it has been reported that the expression CSC markers CD44 and CD166, associated with KRAS mutation in primary colonic tumors, represent a higher risk of lymph node involvement by the tumor and development of liver and lung metastasis [18]. …”
Section: Introductionmentioning
confidence: 99%
“…CD44 is a type 1, 85-200 kDa transmembrane glycoprotein expressed in both normal and tumor tissues [16,27,28]. Discovered initially as a receptor for hyaluronic acid, the molecule has retained its affinity for it and for other components like collagens, osteopontin, or type I metalloproteinase [3,27]. Supplementary, an adhesion function was highlighted for CD44 that was found to intervene in both cell-cell and cell-matrix interactions [4,16].…”
Section: Cd44 In Colon Cancermentioning
confidence: 99%
“…Colon cancer stem cells (CCSCs) are multipotent neoplastic cells that have the ability to differentiate and initiate the carcinogenesis process [3]. Due to their increased viability, CCSCs are responsible for both tumor growth and tumor recurrence [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation